Metropolregion Hamburg - Christian Diller; Jörg Knieling (Raumforschung und Raumordnung, 2003)
There are very few regions in Germany today where the current discussion on future demographic developments is not being conducted against the backdrop of looming shrinkage or — at the very least — stagnation. With a population of over four million, the Hamburg metropolitan region is, however, one of these rare cases. All the signs here augur growth — both in the core city and in the surrounding area. The absence of any evident symptoms of a serious crisis possibly goes some way to explaining why there currently appear to be no significant impulses to embark on further steps towards consolidation of the region. Although clear progress has been recorded over recent years in respect of co-operation within the Hamburg metropolitan region, structural limits exist which cannot be overcome. This article present a critical appraisal of achievements to date and outlines perspectives for the future development of the Hamburg metropolitan region.